HUBUNGAN PERILAKU MEROKOK DAN STATUS GIZI DENGAN KEJADIAN TUBERKULOSIS PARU DI POLI PARU RSUD KOTA DUMAI - Juwita Yanti Pakpahan (Jurnal Kesehatan Husada Gemilang, 2019)
WHO declares the lungs tuberculosis is a global emergency for human. The incident of TB contribute to the high number of deaths in Indonesia. Lungs TB is a disease with several of risk factors which one of them is smoking. It is caused by Mycobacterium tuberculosis. Data of Medical Record of RSUD of Dumai City, the number of cases of lungs TB was 11% (1120 visits and 130 cases of lungs TB) in Pulmonary Poli of RSUD of Dumai City, and the risk factor of is still unidentified. The persistence of the research is to identify the correlation among smoking behavior, nutritional status, and lungs tuberculosis at Pulmonary Poly of RSUD of Dumai City. This research is an analyticalcross sectional. The population of the research were all patients who visited the Pulmonary Poly of RSUD of Dumai City, while the sample was done through the use of Accidental Sampling technique with the number of the patients were 30 people. The bivariate results express the correlation among smoking behavior (p value 0.000), nutritional status (p value 0.000), and lungs tuberculosis. The researcher wishes the respondents reduce smoking, and eat nutritious foods to prevent recurrent lungs TB.